A dustbin structure for building site - Zhou Licheng; Luo Gang; Gan Guopan; Ni Wei; Luo Li (2016)
The utility model discloses a dustbin structure for building site, include the box, be used for horizontal separation or open the partition mechanism of box and be used for taking out domestic waste's temporary storage mechanism, the upper end of box is the opening form, separates the establishment of institution in the box, and the upper portion of separating mechanism and box constitutes a cell body that is used for placing domestic waste, temporary storage mechanism fixes in the box, and temporary storage mechanism is located the below of separating the mechanism. The utility model adopts the above structure, can carry out safe and reliable ground with combustible object such as cigarette end and food plastic bags and handle, help improving the construction environment, stop the potential safety hazard. 本实用新型公开了种用于建筑工地的垃圾箱结构，包括箱体、用于横向阻隔或打开箱体的分隔机构以及用于取出生活垃圾的暂存机构，所述箱体的上端呈开口状，分隔机构设置在箱体内，且分隔机构与箱体的上部构成个用于放置生活垃圾的槽体，所述暂存机构固定在箱体内，且暂存机构位于分隔机构的下方。本实用新型采用上述结构，能够将烟头以及食品塑料袋等易燃物品进行安全可靠地处理，有助于改善施工环境，杜绝安全隐患。